Risky financial collateral, firm heterogeneity, and the impact of eligibility requirements - Matthias Kaldorf; Florian Wicknig (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
This paper studies the effects of making corporate sector assets eligible as collateral for central bank borrowing. Banks are willing to pay collateral premia on assets if they become eligible as collateral. Collateral premia make debt financing cheaper for eligible firms, which respond by increasing their debt issuance. While this has a positive effect on collateral supply, firm responses also have a negative effect: higher debt issuance makes corporate bonds riskier in future periods, which in turn reduces aggregate collateral. We provide a novel analytical characterization of firm responses to eligibility requirements in a heterogeneous firm model with default risk and collateral premia paid on eligible bonds. Using a calibration of the model to euro area data, we study the impact of the ECB's col-lateral easing policy during the 2008 financial crisis and evaluate the quantitative relevance of firm responses. We find that firm responses substantially deteriorate collateral quality and dampen the total increase of collateral supply. Our analysis suggests that a covenant conditioning eligibility on leverage and current default risk is a potentially powerful in-strument to mitigate the adverse impact of collateral premia on default risk and, thereby, to maintain a high level of collateral supply.
Keywords: E44; E58; G12; G32; G33; 330; Collateral Premia; Eligibility Requirements; Firm Heterogeneity; Corporate Default Risk; Collateral Policy